Compound marine heatwaves and tropical cyclones delay the onset of the Bay of Bengal summer monsoon - Xiong Zhou; Kang Xu; Karumuri Ashok; Jian Shi; Lei Zhang; Jin-Yi Yu; Boqi Liu; Chi-Yung Tam; Hongzhou Xu; Weiqiang Wang (npj Climate and Atmospheric Science)
Abstract Marine heatwaves (MHWs) and tropical cyclones (TCs) are prominent extreme events in the Bay of Bengal (BoB), whose co-occurrence can amplify their impacts. This study explores the mechanisms behind compound MHW-TC events and their influence on the onset of the BoB summer monsoon (BoBSM). Our findings indicate that compound MHW-TC events initiate with increased downward shortwave radiation and Ekman downwelling during MHW formation, followed by latent heat flux release and Ekman upwelling during the TC lifecycle. The interaction between increased maximum potential intensity and steering flow during compound events results in a westward shift in TC tracks, delaying precipitation and atmospheric latent heat release in the eastern BoB. These factors, as well as the warmer sea surface temperatures in the BoB, hinder the reversal of the mid-to-upper tropospheric meridional temperature gradient, ultimately postponing BoBSM onset. These insights enhance the understanding of MHW-TC interactions and their implications for predicting BoBSM onset.